Strategic Leadership of Kyai in Traditional Islamic Educational Institutions: Dynamics of Adaptation and Transformational Challenges in Salaf Islamic Boarding Schools - Dian Zulfafatul Iman; Jazilur Rahman (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The accelerating expansion of digital disruption, institutional accountability, and global educational competition has generated profound challenges for faith-based educational institutions, particularly in maintaining religious authenticity while simultaneously developing adaptive and sustainable governance systems. Within traditional Islamic boarding schools (pesantren salaf), these tensions position the kyai not merely as a symbolic religious authority, but as a strategic actor responsible for negotiating institutional continuity, organizational transformation, and educational resilience. Despite the growing literature on pesantren modernization, existing studies remain largely dominated by descriptive and techno-centric perspectives that insufficiently explain how charismatic-theological authority is strategically reconstructed into adaptive institutional governance. This study therefore aims to critically examine the strategic leadership of the kyai at Nurul Qodim Islamic Boarding School and to analyze the dynamics of adaptation and transformational challenges within traditional Islamic educational institutions. Employing a qualitative approach grounded in an interpretive paradigm, this research adopted a single-case study design involving in-depth interviews, participant observation, and institutional document analysis. Participants consisted of kyai, administrators, senior ustaz, alumni, dormitory administrators, and santri selected through purposive sampling. The findings reveal that the strategic leadership of the kyai operates through an integrated hybrid governance system combining charismatic-theological authority, professional educational management, adaptive-transformative leadership, indigenous-transformative values, and collaborative governance mechanisms. The study further demonstrates that institutional transformation within salaf Islamic boarding schools does not occur through the displacement of tradition, but through the strategic reconstruction of religious legitimacy and local cultural values into adaptive institutional capital. Theoretically, this study proposes the concepts of Theo-Managerial Hybridity and Hybrid Resilience as alternative non-Western frameworks for understanding organizational transformation and sustainability within faith-based educational institutions. More broadly, the findings contribute to the global discourse on educational leadership by demonstrating that institutional resilience within traditional religious organizations can emerge through strategic cultural hybridization rather than through secularization or the erosion of spiritual authority.